Pemberdayaan UMKM melalui Literasi Kecerdasan Buatan dan Teknologi Augmented Reality untuk Transformasi Ekosistem Kewirausahaan Digital di Kelurahan Masale Kota Makassar: Penelitian - Amraeni, Amraeni; Alisyahbana, Andi Naila Quin Azisah; Mushaf, Mushaf; Syukur, Pramudya Asoka; Masna, Ummul Khaeri; Andri, Dian Puspita Sari; Isma, A; Dewantara, Hajar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The low level of digital adoption among Micro, Small, and Medium Enterprises (MSMEs), particularly in tax administration and marketing, continues to hinder competitiveness. This community service program focuses on empowering MSMEs in Masale Sub-district, Makassar City through Artificial Intelligence (AI)-based tax literacy and the use of Augmented Reality (AR) for digital promotion. The activity aims to enhance MSME capacity through AI literacy training for tax management and the application of AR in digital marketing strategies. The method used is Participatory Action Research (PAR), implemented through socialization, smart tax and AR content creation training, mentoring, and evaluation using pre-test and post-test. The results show a significant improvement, with the average accuracy increasing from 48.2% in the pre-test to 91.8% in the post-test. This program effectively strengthens MSMEs’ digital skills, improves operational efficiency, and expands AR-based promotional reach, all of which contribute to building a sustainable digital entrepreneurship ecosystem.